MANGANAN: IMPLEMENTATION OF KALYANAMITTA VALUES IN SEDEKAH BUMI TRADITION IN JEPARA - Adhiviyanto, Dirga Yuka Okta; Setyoko, Rahmad (Sekolah Tinggi Agama Buddha Negeri Raden Wijaya, 2024)
Manganan is a tradition passed down from generation to generation by the people of Tunahan village, Jepara district. This research aims to describe the transformation of Kalyanamitta values in the Manganan tradition of Sedekah Bumi in Tunahan village, Jepara district. The methods used in this research are phenomenological methods and descriptive methods. By providing meaning from the experiences that have been felt and also to describe what happened when the research was carried out according to the facts in the field. The research results state that first, the Manganan tradition carried out in Tunahan village is different from the Manganan tradition in general in terms of its implementation, place and also the process carried out; The second result is the values contained in the implementation of the Manganan tradition, including religious values, solidarity values, tolerance values, educational values; Third, there are values contained in the Manganan tradition which are related to Kalyanamitta, namely religious values, tolerance values and solidarity values. The conclusion of this research is that the Manganan tradition which is still carried out today by the Tunahan village community has meaning, values and symbols contained in it and also from the values in the Manganan tradition there is a connection with Buddhist teachings, namely kalyanamitta